Importance of Diversified Marketing Strategies for Fast Food Restaurant Chains - Ekaterina Shcherbakova (Westcliff University, 2020)
Every organization needs to consistently adjust operations and marketing strategies in order to perpetually satisfy consumers and reinforce dedication to the vision and mission of the company. The adjustments need to be made over time, according to situational influences as well as internal and external trends affecting consumer behavior. Without a proper marketing strategy, a company may go out of business due to internal and external organizational pressures. Nowadays, as the economies of countries worldwide show signs of crisis, fast food industry players need to adjust their marketing strategies in order to overcome the competition within new circumstances. This literature review demonstrates that in order to succeed in this competition, food chain companies need to combine multiple approaches and use omni-channel marketing campaigns. This article summarizes the research made over the last two decades and suggests topics in this area that can be further researched. The research documents, reviewed in chronological order, are peer-reviewed articles, conference papers, corporate websites and major media resources.